Mum the entrepreneur - News Straits, Times (New Straits Times, 2013)
THINGS have a way of falling into place, despite what can, sometimes, be overwhelming circumstances. This is what Khairul Noormaaidah Zali, 28, firmly believes. Fondly known as Aida, the charming and petite woman is a familiar face to those who follow reality show Gadis Melayu on TV9. The show features a search for a talk show hostess who embraces Malay culture and tradition, yet is modern in outlook and attitude.